Effects of carnitine on performance of finishing steers - R.H. Greenwood; C.A. Löest; Evan C. Titgemeyer; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2000)
Ninety-five crossbred steers (787 lb initial body weight) were fed finishing diets (14.5% crude protein) for 129 days. Diets were based on steam-flaked corn and contained 6% alfalfa and 4% tallow. Steers were supplemented with 2 g per day of L-carnitine, or not supplemented (control). Feed intakes, gains, and feed efficiencies were not impacted by carnitine supplementation. However, steers receiving L-carnitine had fatter carcasses as indicated by tendencies (P<.2) for more subcutaneous fat, higher marbling scores, and higher yield grades. Carnitine supplementation may increase fat deposition and alter carcass quality of finishing cattle.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Steers; Carnitine; Performance; Carcass quality